OLIY TA’LIM TASHKILOTLARI TALABALARINING MULOQOT KOMPETENSIYALARINI RIVOJLANTIRISH TEXNOLOGIYALARINI TAKOMILLASHTIRISHDA YANGI PEDAGOGIK TEXNOLOGIYALARNIG AHAMIYATI - A.A.Xasanov (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In developing professional communication skills, it is advisable to use professional work on a project, as well as a form of activating thinking in the process of learning a foreign language. This type of activity, on the one hand, is important for students, focused on a specific, real practical result, involves the use of a wide range of problem, research and research methods, and on the other hand, various factors and conditions for solving the problem and implementing the results as a whole involves developing the problem taking into account.